Evaluating Olive oil Quality and Food Safety Compliance in Tirana, Albania, Retail Markets - Risto, Josif; Osmani-Lataj, Leomira; Topi, Dritan (South Eastern European Journal of Public Health, 2025)
The debate over the significance of the quality of fats in our diet has been present in recent decades. Olive oil (OO) is unique among vegetable oils due to its alleged health benefits. Quality assessment, including the traceability of food products through control of the primary compounds, is a key step. Bottled OOs in retail markets have been subject to deceptive labeling, fraud, and adulteration. Health concerns are associated with mixing them with different vegetable oils. We investigated the fatty acid (FA) composition of several bottled olive oils from popular domestic brands in Tirana retail markets, using gas chromatography with a flame ionization detector and gas chromatography-mass spectrometry. This study's results show that olive oils' fatty acid (FA) composition (OOs) does not reflect adulteration. The levels of trans-fatty acids (trans-FAs) were below the threshold established by European Union regulation 2568/91, as amended by 1989/2003. Specifically, oleic acid content ranged from 64.71% to 75.62%, palmitic acid from 8.43% to 14.26%, and linoleic acid from 6.64% to 13.1%. Furthermore, linolenic acid levels were below 1%, indicating that mixing with other vegetable oils is not evident. The trans-FA levels aligned with the label information, and the linolenic acid values were between 0.38% and 0.94%. The fatty acid profile of these olive oils demonstrated low saturated FA levels and a high concentration of monounsaturated FA. Our findings indicate that bottled olive oils from the Kalinjoti cultivar are appropriate for marketing as mono-cultivar brands. However, this is not advisable for bottled olive oils from Nisioti and Bardhi Tirana cultivars because they exhibit lower oxidative stability. .